E-Cadherin in 1-Methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine-Induced Parkinson Disease. (17th April 2016) - Cataldi, Samuela; Codini, Michela; Hunot, Stéphane; Légeron, François-Pierre; Ferri, Ivana; Siccu, Paola; Sidoni, Angelo; Ambesi-Impiombato, Francesco Saverio; Beccari, Tommaso; Curcio, Francesco; Albi, Elisabetta
Abstract : Today a large number of studies are focused on clarifying the complexity and diversity of the pathogenetic mechanisms inducing Parkinson disease. We used 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP), a neurotoxin that induces Parkinson disease, to evaluate the change of midbrain structure and the behavior of the anti-inflammatory factor e-cadherin, interleukin-6, tyrosine hydroxylase, phosphatase and tensin homolog, and caveolin-1. The results showed a strong expression of e-cadherin, variation of length and thickness of the heavy neurofilaments, increase of interleukin-6, and reduction of tyrosine hydroxylase known to be expression of dopamine cell loss, reduction of phosphatase and tensin homolog described to impair responses to dopamine, and reduction of caveolin-1 known to be expression of epithelial-mesenchymal transition and fibrosis. The possibility that the overexpression of the e-cadherin might be implicated in the anti-inflammatory reaction to MPTP treatment by influencing the behavior of the other analyzed molecules is discussed.